2017
DOI: 10.1111/cas.13423
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of local renin‐angiotensin system in immunosuppression of tumor microenvironment

Abstract: To improve current cancer immunotherapies, strategies to modulate various immunosuppressive cells including myeloid derived suppressor cells (MDSC) which were shown to be negative factors in immune‐checkpoint blockade therapy, need to be developed. In the present study, we evaluated the role of the local renin‐angiotensin system (RAS) in the tumor immune‐microenvironment using murine models bearing tumor cell lines in which RAS was not involved in their proliferation and angiogenetic ability. Giving angiotensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 50 publications
1
57
0
Order By: Relevance
“…In vitro and in vivo studies have further revealed that these anticancer effects of ARB include direct suppression of cancer growth and increase of antitumor immunity [ 35 38 ]. Nakamura et al showed that administration of ARB to colon cancer-bearing mice induced the expansion of cancer-specific CTLs and reduced the levels of immune-suppressive cytokines, interleukin-6 (IL-6), IL-10, vascular endothelial cell factor, and arginase in the tumor microenvironment [ 39 ]. They demonstrated that combination therapy with ARB and anti PD-L1 antibody significantly reduced tumor size, suggesting that this therapy is also useful in clinical setting.…”
Section: Immunomodulatory Effects Of Drugs Used For Treating Commomentioning
confidence: 99%
“…In vitro and in vivo studies have further revealed that these anticancer effects of ARB include direct suppression of cancer growth and increase of antitumor immunity [ 35 38 ]. Nakamura et al showed that administration of ARB to colon cancer-bearing mice induced the expansion of cancer-specific CTLs and reduced the levels of immune-suppressive cytokines, interleukin-6 (IL-6), IL-10, vascular endothelial cell factor, and arginase in the tumor microenvironment [ 39 ]. They demonstrated that combination therapy with ARB and anti PD-L1 antibody significantly reduced tumor size, suggesting that this therapy is also useful in clinical setting.…”
Section: Immunomodulatory Effects Of Drugs Used For Treating Commomentioning
confidence: 99%
“…Most preclinical mouse models investigating the immune composition of CRC tumors are based on the implantation of colon tumor cell lines under the skin [35,36]. Nevertheless, our past work has revealed that the skin microenvironment does not accurately reproduce the microenvironment of organs from which tumor cells originate [9].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Shen J. et al, 2016). It is shown that microenvironment tumor cells from mice immunized colon cancer cells, by promoting the escape of anticancer immunity, formed by macrophages and cancer-associated fibroblasts (Nakamura K. et al, 2018). According to the authors, a sharp increase in the level of expression of ACE macrophages may indicate to increase local production of the intensity of immunosuppressive molecules, such as nitric oxide, TGF-b1, PGE2.…”
Section: Angiotensin-i-converting Enzyme (Ace-1)mentioning
confidence: 99%